Impact of Mindfulness-Based Parenting on Women in Treatment for Opioid Use Disorder. Issue 5 (September 2017) - Gannon, Meghan; Mackenzie, Michael; Kaltenbach, Karol; Abatemarco, Diane
Abstract : Objectives: Mothers with opioid use disorder are at high risk for maladaptive parenting. The present observational study aimed to measure the impact of a trauma-informed mindfulness-based parenting (MBP) intervention on quality of parenting behaviors of mothers primarily with opioid use disorders as well as examine associations between exposure to adverse childhood experiences and self-reported mindful parenting. Methods: A pretest posttest design was used with repeated measures. A total of 160 women were recruited from a substance use treatment program into the 12-week-long group-based intervention comprised didactic and experiential mindfulness activities. The Keys to Interactive Parenting Scale (KIPS) measured quality of parenting behavior, the Adverse Childhood Experiences Tool captured history of exposure to childhood trauma, and the Interpersonal Mindfulness in Parenting (IM-P) scale measured the degree of mindful parenting. Analyses were conducted using multilevel modeling. Results: The MBP intervention resulted in clinically significant improvements in KIPS total and all subscale scores and an IM-P total score. Data showed higher baseline Adverse Childhood Experiences and higher program attendance significantly predicted improved overall quality of parenting behaviors at a greater rate over time. Higher IM-P scores were associated with greater rate of improvement in KIPS total and all subscale scores. Conclusions: Study findings suggest a trauma-informed MBP intervention for parenting women with opioid use disorders is associated with significant clinical improvements in quality of parenting behavior. Results of this model show promise in supporting parenting of mothers receiving treatment for opioid use disorders to enhance bonding and parenting.